Constraints Faced by Pineapple Growers in Tripura - Roy, Priyanka; Ghosh, Souvik (Indian Journal of Extension Education, 2022)
Agriculture is the main occupation of the inhabitants in Tripura and 80 per cent of the rural people depend on agriculture and allied sectors for the economic, food and nutritional security. Tripura has got highly suitable agro-climatic conditions to grow pineapple fruit. Livelihoods of many farmers largely depend on pineapple cultivation. However, pineapple cultivation is not delivering the desired output as it is constrained by several factors. Present study was conducted in year 2021 to delineate various constraints of pineapple cultivation and to determine difficulty level of each constraint as perceived by a random sample of 80 farmers. Various constraints were categorized as situational, technological, economic, social, environmental, infrastructure, and market related constraints. The major constraints identified were low rainfall, scarcity of water, labour intensiveness, high labour wage, high cost of cultivation, low adoption of scientific practices by neighbouring farmers, lack of group approach in farming, lack of infrastructure like; soil testing laboratory, agro-service centre, storage facilities and low-quality packaging. Lack of organised marketing facilities was the major concern for respondents-farmers. Future policy advocacies and agroadvisories for development of pineapple cultivation need to focus on combating aforesaid constraints in pineapple cultivation.